Current status of hybrid intravascular ultrasound and optical coherence tomography catheter for coronary imaging and percutaneous coronary intervention. Issue 5 (May 2021) - Terashima, Mitsuyasu; Kaneda, Hideaki; Honda, Yasuhiro; Shimura, Tetsuro; Kodama, Atsuko; Habara, Maoto; Suzuki, Takahiko
Highlights: Limitations of single use of intravascular ultrasound (IVUS) or optical coherence tomography (OCT) for evaluation of coronary artery disease. Usefulness and limitations of sequential use of IVUS or OCT. Advances in hybrid IVUS-OCT imaging devices. Clinical application and usefulness of hybrid IVUS-OCT imaging devices. Abstract: Both intravascular ultrasound (IVUS) and optical coherence tomography (OCT) play a crucial role in elucidating the pathophysiology of coronary artery disease (CAD) with the goal to improve patient outcomes of medical and/or interventional CAD management. However, no single intravascular imaging technique has been proven to provide complete and detailed evaluation of all CAD lesions due to some limitations. Although sequential use of multiple modalities may sometimes be performed, there may be issues related to risk, time, and cost. To overcome these problems, several hybrids involving dual-probe combined IVUS-OCT catheters have been developed. The aim of this review article is to demonstrate some limitations of stand-alone imaging devices for evaluation of CAD, summarize the advances in hybrid IVUS-OCT imaging devices, discuss the technical challenges, and present the potential value in the clinical setting, especially in patients receiving medical or interventional CAD management.